Erratum – The 50th Anniversary of the Committee on Acoustics of the Polish Academy of Sciences - RAKOWSKI, Andrzej; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 2014)
In the article “The 50th Anniversary of the Committee on Acoustics...” in the 3rd issue Archives of Acoustics, 2014 the authors have omitted an important detail (p. 303, line 18) namely: Halina Ryffert (1969–1971).